Fleshed Networks: Exhibition Documentation (2025), WebXR Experience on the STYLY Platform for Constellations, ISEA (International Symposium of Electronic Art), Brisbane 2024 - Megan Beckwith (4980779) (2025)
Fleshed Networks is a WebXR experience created by Dr Megan Beckwith for Constellations, the online exhibition program of the International Symposium of Electronic Art (ISEA2024) in Brisbane. This documentation captures the 2025 exhibition version of the work, presented on the STYLY platform as part of ongoing research into digital dance, virtual performance, and posthuman embodiment. The work presents a non-linear narrative environment in which users encounter a visceral network of hybrid bodies, cyborg forms composed of human and non-human elements. These purple, fleshy structures embed both technical and organic parts and appear to observe the user from multiple vantage points. The environment explores shifting relationships between the real and virtual, challenging traditional notions of presence, temporality, and perception. Within Fleshed Networks, the concept of “now” is reimagined. Users experience dual and concurrent forms of presence: the physical body remains in real space while its avatar navigates the virtual realm. This simultaneous embodiment disrupts linear understandings of time and space, creating a fluid and multi-layered temporal experience. As a practitioner whose work merges dance, 3D animation, motion capture, and XR technologies, Beckwith situates Fleshed Networks within transmedia performance research and the evolving field of AI-mediated creative practice. This Figshare entry includes documentation of the installation and related media materials for research, archiving, and public access.